Surfactant Dysfunction - Gower, W. Adam (2011)
Mutations in genes encoding proteins needed for normal surfactant function and metabolism cause acute lung disease in newborns and chronic lung disease in older children and adults. While rare these disorders are associated with considerable pulmonary morbidity and mortality. The identification of genes responsible for surfactant dysfunction provides clues for candidate genes contributing to more common respiratory conditions, including neonatal respiratory distress syndrome and lung diseases associated with aging or environmental insults. While clinical, imaging and histopathology features of these disorders overlap, certain features are distinctive for surfactant dysfunction. Natural histories differ depending upon the genes involved and a specific diagnosis is important to provide accurate information concerning prognosis and mode of inheritance. Diagnosis of surfactant dysfunction can be made by biopsy, but identification of the specific gene involved requires molecular genetic testing, which is non-invasive. Currently there are no effective medical treatments for surfactant dysfunction. Development of therapies is a priority for research, which may benefit patients with other lung diseases.